Addressing the Challenges in Medical Training for Occupational Health in India's Rapidly Industrializing Landscape (International Journal of Occupational Safety and Health, 2025)
India's rapid industrialization demands an equally robust occupational health framework, yet medical training in this field remains inadequate. With over 250 million industrial units, worker health is crucial for productivity and economic growth. Despite legislative efforts like the Factories Act and ESI Act, challenges persist, including limited practical training, lack of faculty expertise, and the complexities of adult learning. ESIC Medical College, Faridabad, has pioneered hands-on AFIH training to bridge these gaps. Key recommendations include integrating occupational health into MBBS, faculty CME programs, interdisciplinary collaboration, ethical considerations, and mental health sensitization. Strengthening medical education is vital for safeguarding India's workforce.